2019
DOI: 10.9770/jesi.2019.7.1(15)
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of good corporate governance model and auditor independence in earnings' quality improvement

Abstract: The general objective of this research is to explore the model of earnings quality monitoring and to examine the effect of auditor independence on the relationship between corporate governance mechanism and earnings quality. Specifically, this research is aimed to investigate the impact of ownership structure, commissioner board structure, audit committee structure, internal audit function, and internal control activity, on earnings quality by involving an interaction of these variables with auditor independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
1
21
3
4
Order By: Relevance
“…If the risks and challenges cannot be managed properly, then it can result in losses, especially in the financial industry (Soewarno & Mahyarni, 2018). Corporate governance mechanisms are needed to ensure that a company is performing well without abuse (Arniati et al, 2019).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the risks and challenges cannot be managed properly, then it can result in losses, especially in the financial industry (Soewarno & Mahyarni, 2018). Corporate governance mechanisms are needed to ensure that a company is performing well without abuse (Arniati et al, 2019).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…In this context, the company is expected to be profitable as profit is one of the key indicators of successful governance. Profit is the measure which attracts the most attention when assessing the success of a company's management (Arniati et al, 2019;Siddique et al, 2020). Given that profit is commonly used as the indicator of management success, managers may have as strong intention to perform in various ways that will positively influence the reported profits.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report, managerial ownership has an impact on Earning Quality. Arniati et al (2019) conducted the same research and concluded that the Independent Board of Commissioners impacted Earning Quality. According to Hamdan (2020) and Mahdi et al (2020).…”
Section: Introductionmentioning
confidence: 96%
“…Some of them examined governance related to specific functions, such as financial, audit, procurement functions. Some of them concentrated mainly on top management and board of directors (Chen and Shapiro, 2011;Dipendra, 2016;Nourredine and Brahim, 2017;Arniati et al, 2019;Agnihotri and Gupta, 2019;Awadallah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mishra and Mohanty (2018) highlighted that the association between corporate governance and companies' financial performance is debatable. Arniati et al (2019) indicated that the earnings quality-monitoring model is constructed from many variables' interaction. The governance mechanism incorporates ownership, commissioner board, audit committee and internal audit function, and internal control activity.…”
Section: Introductionmentioning
confidence: 99%